2005
DOI: 10.1007/s11173-005-0177-0
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Cu(II) with Hetarylformazanes in Solutions, Polycrystals, and Modified Anionite

Abstract: The reactions of formazanes with transition metal ions can give coordination compounds of different nature and structures, namely, mono-and binuclear complexes, complexes with different surrounding of a central atom and configuration. The reason for such a variety lies in a high flexibility of formazanes, their capability to act as bi-, tri-, or tetradentate ligands with allowance for the substituents [1].Formazanes and their compounds are widely used in chemistry, in particular, as analytical reagents. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…85 It was found that depending on the nature of the substituents at the N(1) atom, the copper atom acquires a squareplanar or a pseudo-tetrahedral configuration. For L 2 Cu complexes prepared in an excess of a ligand, the coordination unit CuN 4 formed contained the N(1) and N(5) atoms of formazan (see structure 37).…”
Section: Formazan Complexes With Metals: Structures and Applicationsmentioning
confidence: 99%
“…85 It was found that depending on the nature of the substituents at the N(1) atom, the copper atom acquires a squareplanar or a pseudo-tetrahedral configuration. For L 2 Cu complexes prepared in an excess of a ligand, the coordination unit CuN 4 formed contained the N(1) and N(5) atoms of formazan (see structure 37).…”
Section: Formazan Complexes With Metals: Structures and Applicationsmentioning
confidence: 99%
“…The ESR data show the square-planar structure of the coordination core Cu³4N³ for formazanate VIIIp and Cu³3N, O³ for VIIp, similarly to the initial complexes VIII and VII [8,9]. Presumably, immobilization of formazanates IV3VI on the polymeric support does not change the structure of the coordination core.…”
Section: Methodsmentioning
confidence: 67%
“…All the compounds are crystal solvates with ethanol. The electronic absorption spectra of complexes IV3VIII in ethanol are The ESR spectra of copper(II) formazanates in toluene [8] suggest formation of a Cu³4N³ distorted tetrahedron for V, Cu³4N³ square-planar structure for VIII, and mixed nitrogen3oxygen Cu³3N, O³ structure for VII.…”
Section: Methodsmentioning
confidence: 99%